ANÁLISE FRACTAL DA RUPTURA MECÂNICA DE PORCELANAS - Mvumbi, Charles Betuel Mansende (2016)
The ceramic porcelains are produced from natural raw materials (silica, feldspar and kaolin). In some applications other materials are added to increase the mechanical and dielectric strength. They are used in the manufacture of several products. Therefore, they are very studied and have been developed for long time. In this work, porcelains with different compositions were characterized and submitted to fragmentation by mechanical disruption in a ballistic impact testing. Generally the mechanical disruption in the materials produces a power dissipation forming cracks and fracture surfaces having an irregular geometry. The main objective of this work was to characterize the microstructure and the fractal fracture surface in porcelains. For comparison, the impact tests were also performed on commercial glass and acrylic. The evaluation of the fracture surface and the fractal dimension of rupture was performed by analyzing the fraction of the fragments as a function of the probability of fracture. The samples were prepared in the form of cylindrical disks with a thickness and fixed diameters. Mechanical impact test was made on the center of the disks for different materials, maintaining the same test conditions. The results of the size and mass of the fragments were obtained as a function of the impact energy, thickness, diameter and kind of material. Thus, it was possible to obtain a correlation between the test conditions and the composition of the material with the fractal pattern breakage. It has been found that the compositions used in porcelain, has a fracture toughness which is between the glass and acrylic. A correlation between strength properties to the patterns of formed crack was made. It was noticed that the number, the shape of cracks and the branches form a pattern that is associated with the impact energy and material type.